Pengaruh Rasio Profitabilitas & Solvabilitas terhadap Harga Saham Perusahaan SubSektor Makanan dan Minuman yang Terdaftar di BEI Periode 2017-2021 - Holifah, Siti; Situngkir, Tiar Lina (J-MAS (Jurnal Manajemen dan Sains), 2024)
The purpose of this study is to investigate how debt to equity ratio and return on equity affect the stock price of publicly traded food and beverage companies on the Indonesia Stock Exchange between 2017 and 2021. This research technique takes a quantitative approach. For this investigation, eight food and beverage companies listed on the Indonesia Stock Exchange were carefully selected using a purposeful selection technique. From 2017 to 2021, sampling was carried out every three months. SPSS 27 software, which consists of a number of tests including traditional assumption tests, was then used to evaluate the data. Normality, multicollinearity, autocorrelation, and heteroscedasticity of the data were assessed with this test. Furthermore, the coefficient of determination, partial test, simultaneous test, and descriptive statistical test were run. The results of this study indicate that in the period from 2017 to 2021, the variables Return on Equity and Debt to Equity Ratio will partially and simultaneously affect the stock price of food and beverage companies listed on the Indonesia Stock Exchange.